2018
DOI: 10.3389/fimmu.2018.02261
|View full text |Cite
|
Sign up to set email alerts
|

The G2A Receptor Controls Polarization of Macrophage by Determining Their Localization Within the Inflamed Tissue

Abstract: Macrophages are highly versatile cells, which acquire, depending on their microenvironment, pro- (M1-like), or antiinflammatory (M2-like) phenotypes. Here, we studied the role of the G-protein coupled receptor G2A (GPR132), in chemotactic migration and polarization of macrophages, using the zymosan-model of acute inflammation. G2A-deficient mice showed a reduced zymosan-induced thermal hyperalgesia, which was reversed after macrophage depletion. Fittingly, the number of M1-like macrophages was reduced in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Here, we demonstrated that G2A-deficient mice showed a strongly reduced infiltration of immune cells at the site of injury. Consistent with our findings, earlier studies also showed a reduced number of macrophages at the inflammatory site during peripheral inflammatory pain [ 22 ]. Interestingly, in dextran sulfate sodium (DSS)-induced colitis, a reduced number of T cells was observed in G2A-deficient mice, confirming our data of the sciatic nerve after nerve injury ( Figure 2 C) [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Here, we demonstrated that G2A-deficient mice showed a strongly reduced infiltration of immune cells at the site of injury. Consistent with our findings, earlier studies also showed a reduced number of macrophages at the inflammatory site during peripheral inflammatory pain [ 22 ]. Interestingly, in dextran sulfate sodium (DSS)-induced colitis, a reduced number of T cells was observed in G2A-deficient mice, confirming our data of the sciatic nerve after nerve injury ( Figure 2 C) [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…Since the number of macrophages was dramatically decreased in G2A-deficient mice in all three investigated tissues (sciatic nerve, DRGs and spinal cord), we hypothesized that G2A-deficiency affects the immunomodulatory and migratory properties of macrophages [ 22 ]. Therefore, we performed a global proteome analysis using a vanguard mass-spectrometry-based approach [ 33 ] using bone marrow-derived macrophages (BMDM) of wild-type and G2A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations